Particulate matter adheres to human hair exposed to severe aerial pollution: consequences for certain hair surface properties. (26th September 2017) - Galliano, A.; Ye, C.; Su, F.; Wang, C.; Wang, Y.; Liu, C.; Wagle, A.; Guerin, M.; Flament, F.; Steel, A.
Abstract: Background: The deposit and adherence of particulate matter (PM) from aerial pollution onto the surface of human hair is a poorly studied phenomenon. Objectives: (i) To reproduce in vitro the deposit of known PM on standardized hair swatches in a closed box, (ii) to compare in vitro data with those obtained under 'real‐life' conditions of severe aerial pollution and (iii) to assess the changes of the hair surface properties, potentially caused by the adherence of airborne PM onto the hair. Methods: In vitro: a PM was sprayed onto untreated or sebum‐coated hair swatches. Real‐life conditions : other swatches were exposed to a severely polluted environment, for 24 to 72 h, in Baoding (PR China). In both cases, swatches were examined using scanning electron microscopy. The shine, the frictional properties and the level of metals were measured and compared to those same properties for the unexposed swatches. Results: This work clearly indicates that, under real‐life conditions, a large number of PM of various sizes are deposited onto the hair surface. This phenomenon is increased by the presence of sebum and longer exposure times. The in vitro level of PM deposited onto the hair surface is comparable to the in vivo level. The presence of sebum seems to favour the deposit of larger PM. The shine of the exposed swatches is significantly decreased, whereas their respective friction coefficients are significantly increased. Both the presence of sebum and length of exposure time increased the amount of analysed metals present on the exposed hair surface (Al, Fe, Cu, Ba and Zn). Conclusion: This work indicates that a very high amount (e.g. billions) of PM can be deposited on a full head of hair for subjects living in a severely aerially polluted environment. This process can be reproduced in vitro . In real‐life, pollution has a strong impact on hair surface properties, leading to a modification of the visual aspect (loss of shine) and the alteration of hair surface (increase in friction force). This work may be used to pave the way for prevention and cleansing studies in the field of hair care. Abstract : For subjects living in a severely aerially polluted environment, billions of PM can be deposited on a full head of hair. We show that such process can be reproduced in vitro. Pollution has a strong impact on hair surface properties, leading to a modification of the visual aspect (loss of shine) and the alteration of hair surface (increase in friction force).